(untitled) (American Journal of Physical Education and Health Science, 2024)
This study explores the multifaceted perspective of gay and lesbian athletes participating in sports, specifically focusing on their challenges and coping mechanisms. A total of six (6) gay and lesbian athletes engaged in various sports were subjected to semi-structured interviews to investigate the impact of their experiences during sports participation and the development of their coping mechanisms. Despite growing endeavors towards acceptability and inclusion within the realm of sport participation, gay and lesbian athletes continue to face substantial challenges related to negative thoughts and feelings and social problems. Findings suggest that gay and lesbian athletes conceal their sexual orientation, actively seek support from peers, family, and coaches, and develop a strong sense of identity to navigate these challenges effectively. Moreover, it examines the coping mechanisms employed by gay and lesbian athletes to overcome these challenges, such as self-affirmation, establishing relationships, and coping strategies. Through exploration of these challenges and coping mechanisms, this study aims to shed light on the complexities of gay and lesbian athletes’ experiences in sports and provide valuable insights for fostering greater enhanced inclusivity and support networks within sports communities.